Effects of glucocerebrosidase gene variations on the risk of Parkinson’s disease dementia: a meta-analysis - Li, Qiujie; Bi, Zhumei; Liang, Weiming; Yin, Shan; Li, Huaicheng; Liang, Zhongyou; Wu, Minyao; Quan, Jieru; Li, Cheng (Frontiers in Aging Neuroscience, 2025)
ObjectiveThis meta-analysis aimed to investigate the effects of glucocerebrosidase gene (GBA) variations on the risk of Parkinson’s disease dementia (PDD) and to identify the relationship between GBA variations and PDD.MethodA comprehensive search was performed to retrieve publications from PubMed, Cochrane Library, Embase and Web of Science up to March 19, 2025. The search terms included “glucocerebrosidase,” “Parkinson’s disease,” and “dementia.” After rigorous screening, cohort studies were included for meta-analysis.ResultsThis meta-analysis revealed a significant overall association between the presence of GBA variation and an increased risk of dementia in PD patients (RR = 1.82, 95% CI: 1.52–2.18, p < 0.00001). When stratified by variant type, carriers of GBA mutations exhibited a similar elevation in dementia risk (RR = 1.82, 95% CI: 1.49–2.23, p < 0.00001), and carriers of GBA polymorphisms also demonstrated a heightened risk (RR = 1.82, 95% CI: 1.26–2.61, p = 0.001). Analysis of specific mutations revealed that the N370S variant was associated with an increase in dementia risk (RR = 1.54, 95% CI: 1.24–1.92, p < 0.0001), whereas the L444P variant conferred a stronger effect (RR = 2.17, 95% CI: 1.74–2.71, p < 0.00001). Additionally, the E326K polymorphism was also significantly associated with an increased risk of dementia (RR = 2.34, 95% CI: 1.88–2.91, p < 0.00001).ConclusionGBA variations are significant risk factors for PDD, with varying degrees of risk conferred by different variants. These findings underscore the critical role of GBA in the pathogenesis of PDD and highlight its potential as a key genetic risk factor.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?, Identifier CRD420251109378.